The Effectiveness of Genre-Based Approach Learning in Improving Critical Thinking Skills in English Language Learning - Idawati Situmorang (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Students' low critical thinking skills are caused by one-way learning, where students only receive material and a lack of variety in the application of learning models, especially those that encourage critical thinking. This study aims to determine the effect of the Genre-Based Approach learning model on improving the thinking skills of AMIK Parbina Nusantara students in English courses. This research method was pre-experimental, using only the experimental group without a control group. The research design used a One Group Pretest-Posttest Design. The data collection techniques used were tests and questionnaires. Data analysis techniques used descriptive statistical analysis, normality tests, t-tests, and hypothesis testing. The results showed a significant effect of the application of the Genre-Based Approach learning model on students' critical thinking skills. The results of the research that has been conducted obtained the results of the initial ability or pretest of students an average of 42.33 and after being given treatment using the Genre Based Approach learning model, the average result was 72.33. Based on the results of the study, it can be concluded that H0 is rejected and H1 is accepted, which means there is a significant influence between the Genre Based Approach learning model and students' thinking abilities in English lectures.